2020
DOI: 10.3390/catal10060629
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Cells of Yarrowia lipolytica Applied in “One Pot” Indolizine Biosynthesis

Abstract: A series of yeast strains was tested in order to evaluate their catalytic potential in biocatalysis of one-pot indolizine’s synthesis. Yeast cultivation was performed in a submerged system at 28 °C for 72 h at 180 rpm. An assessment of the reagents’ toxicity on yeast viability and metabolic functionality concluded that the growth potential of three Yarrowia lipolytica strains were least affected by the reactants compared to the other yeast strains. Further, crude fermentation products (biomass and cell-free su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Botezatu et al [31] investigated the ability of different yeast strains to catalyze the synthesis of indolizine derivatives. The compounds of interest possess heterocyclic ring cores and may exhibit precious biological activities.…”
Section: Substratementioning
confidence: 99%
See 2 more Smart Citations
“…Botezatu et al [31] investigated the ability of different yeast strains to catalyze the synthesis of indolizine derivatives. The compounds of interest possess heterocyclic ring cores and may exhibit precious biological activities.…”
Section: Substratementioning
confidence: 99%
“…At the same time, the application of biomass revealed that it can be used as a biocatalyst, but its reactions were weaker than the supernatant. Furthermore, the presence of methoxyl or nitro substituents impacted the final yields of bis-indolizines, which were about 50% [31]. On the other hand, Zieniuk et al [32] investigated freeze-dried Y. lipolytica biomass and freeze-dried supernatant in ethyl hydrocinnamate synthesis.…”
Section: Substratementioning
confidence: 99%
See 1 more Smart Citation
“…Indolizines have been synthesized by lipases from Candida antarctica [18]. Botezatu et al [19] used whole cells to catalyze a multicomponent reaction of activated alkynes, α-bromo-carbonyl reagents and 4,4 -bipyridine in the synthesis of bis-indolizines. Several yeast strains were tested to evaluate the effect of the reactants on their physiological activity.…”
mentioning
confidence: 99%